(untitled) (Journal of Economic Research & Business Administration, 2026)
In the context of the accelerated digital transformation of the economy, the problem of youth unemployment is becoming one of the significant challenges to the sustainable socio-economic development of the regions. The spread of digital technologies, the development of online employment platforms and changes in the demand structure for professional competencies are creating new conditions for the integration of young people into the labor market, while increasing interregional differences in the unemployment rate. The purpose of the study is to identify and quantify regional socio-economic factors influencing the level of youth unemployment in the context of the digitalization of the economy, as well as to substantiate the directions of its reduction, taking into account regional specifics. The methodological basis of the research consists of methods of economic and statistical analysis. The empirical basis was the official data of the Bureau of National Statistics (BNS). The work uses an analysis of the dynamics of labor market indicators, comparative regional analysis, correlation analysis and econometric modeling based on panel data. The results of the study showed that the level of economic activity of young people, the level of socio-economic development of regions, as well as the development of digital infrastructure and the availability of digital services have a statistically significant impact on the level of youth unemployment. It has been established that regions with a more developed digital environment are characterized by lower rates of youth unemployment. The results obtained expand the scientific understanding of the impact of digitalization on the transformation of regional labor markets and can be used in the development of state youth policy, improvement of regional employment programs and the development of digital competencies of youth. Keywords: digital transformation of the economy, youth unemployment, regional development, labor market, youth employment.